PERAN GURU DALAM MENGEMBANGKAN KURIKULUM MERDEKA: ERA DIGITALISASI - Suryani, Ade; Yundra, Dede; Artanti, Masyunila; Ramadhan, Syahrudi; Erni, Erni (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2024)
The emergence of technology in the era of globalization has changed all areas of life, including education. Education will experience changes following current developments so as not to be left behind. One step in dealing with technological developments is to update the curriculum. Curriculum changes that often change from time to time have an impact on the way learning takes place in schools. The curriculum provides guidance for teachers to design learning activities that are in accordance with the needs and demands of the times. Curriculum changes are made to update or improve the quality of education. By updating lesson materials or adding the latest content that is relevant to the current era. The role of a teacher is needed in implementing the current curriculum, namely the independent curriculum. The purpose of this study is to describe the role of teachers in implementing the independent curriculum in the digital era. This study uses a qualitative method with a literature review study, namely collecting data from journals or articles that are relevant to the topic. The results of this study are that teachers play an important role in implementing the independent curriculum in learning that provides various benefits to students and improves the quality of education